Investigating Eva’s Trauma in Ramsay’s We Need to Talk about Kevin through Psychoanalysis - Naila Aisyah Utami; Nandy Intan Kurnia (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2025)
Sometimes people easily judge other people’s suffering as a single traumatic event without realizing that trauma can shape the victims’ identity and emotional ability. Thus, this study aims to identify the main character, Eva’s imbalanced personality, its types, and the impacts of trauma on her mental health and well-being as seen in Lynne Ramsay’s We Need to Talk About Kevin (2011) movie. This study applied Sigmund Freud's psychoanalysis theory (1923) to answer the research objectives, focusing on the structural model of the psyche and its relation to Eva’s traumatic experiences. This qualitative research uses Lynne Ramsay’s movie entitled We Need to Talk About Kevin, published in 2011 by BBC Films, as the data source. The data were in the form of scenes and dialogues related to (1) the nature of the main character Eva’s imbalanced personality, (2) the types of traumas experienced by her, particularly in relation to her son Kevin, and (3) the impacts of the trauma on Eva’s psychological and overall well-being. The researchers were the primary instrument of this study, conducting a close reading of the movie and analyzing the data through a psychoanalytic lens. The results of this study reveal that the main character's personality is dominated by her superego, which leads her to have acute, chronic, and complex traumas.These traumas resulted in PTSD, emotional distress, dissociation, and physical symptoms. Therefore, through the lens of Freud’s psychoanalysis, combined with the trauma theory and film analysis, this study uncovers that someone’s suffering should be seen as an ongoing psychological process. Moreover, this study shows that psychoanalytic theory can be applied to film, which then broadens the scope of psychoanalytic literary criticism.